2021
DOI: 10.12669/pjms.37.3.3078
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of burnout and associated factors among medical educators

Abstract: Objective: To assess burnout in medical educators and to identify factors associated with it. Methods: A sequential mixed methods research study was conducted over eight months from July 2018 until February 2019. Participants included medical educators, who are studying for or graduated with a postgraduate qualification in medical education. An online questionnaire was developed using Maslach Burnout Inventory to collect quantitative data. The findings were explored in-depth qualitatively. Descriptive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
(27 reference statements)
1
8
1
1
Order By: Relevance
“…Similar findings were obtained from a study in Pakistan. 26 On the other hand, a Korean study was done among clinical faculty members of the School of Medicine, and the results of the Korean study showed lower burnout values which opposed the results of our study. This was attributed to higher scores of professional self-concept which means a perception of oneself as a member of the profession.…”
contrasting
confidence: 99%
“…Similar findings were obtained from a study in Pakistan. 26 On the other hand, a Korean study was done among clinical faculty members of the School of Medicine, and the results of the Korean study showed lower burnout values which opposed the results of our study. This was attributed to higher scores of professional self-concept which means a perception of oneself as a member of the profession.…”
contrasting
confidence: 99%
“…In this study, cited as the first comparison of burnout scores before and after the pandemic in a national pediatric subgroup, nearly 40 percent of respondents felt that their contribution to the COVID-19 pandemic was underestimated by their institutions ( 7 ). In a study, Akram et al ( 25 ) reported very high levels of burnout among Pakistani clinical faculty members from July 2018 to February 2019. In a study to examine the burnout of physicians working at a hospital in São Paulo, Brazil, in the COVID-19 pandemic, Fumis et al reported it as high ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 Medical Educationists, a discipline of basic sciences from all over Pakistan, showed a moderate level of burnout, and the results are consistent with our study. 1 The available literature indicates that the faculty of basic sciences is facing a moderate burnout level, which needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout is the condition where a worker's ability to perform is reduced and is associated with stress and lack of self-satisfaction leading to a negative impact on the physical and mental health of that individual. 1 Job performance is negatively affected by the level of burnout of the employee. 2 Burnout has been associated with many physical, psychological and occupational consequences, indicating that necessary measures should be taken to avoid the negative impact of burnout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation